Structural and functional reconstitution of inner dynein arms in Chlamydomonas flagellar axonemes (The Rockefeller University Press, 1992)
The inner row of dynein arms contains three dynein subforms. Each is distinct in composition and location in flagellar axonemes. To begin investigating the specificity of inner dynein arm assembly, we assessed the capability of isolated inner arm dynein subforms to rebind to their appropriate positions on axonemal doublet microtubules by recombining them with either mutant or extracted axonemes missing some or all dyneins. Densitometry of Coomassie blue-stained polyacrylamide gels revealed that for each inner dynein arm subform, binding to axonemes was saturable and stoichiometric. Using structural markers of position and polarity, electron microscopy confirmed that subforms bound to the correct inner arm position. Inner arms did not bind to outer arm or inappropriate inner arm positions despite the availability of sites. These and previous observations implicate specialized tubulin isoforms or nontubulin proteins in designation of specific inner dynein arm binding sites. Further, microtubule sliding velocities were restored to dynein-depleted axonemes upon rebinding of the missing inner arm subtypes as evaluated by an ATP-induced microtubule sliding disintegration assay. Therefore, not only were the inner arm dynein subforms able to identify and bind to the correct location on doublet microtubules but they bound in a functionally active conformation.